Complete business statistics - Aczel Amir D. (The McGraw-Hill/Irwin series Operations and decision sciences, 2006)
Offering diverse, real-world problems drawn from a variety of international sources, including finance, marketing, government, sports, retail, and real estate, this book aims to challenge students to develop a realistic sense of how statistics can be applied in business situations.